Adansonia digitata fruit: compounds and antioxidante activity against reactive species - Pinto, Diana (2021)
Baobab (Adansonia digitata) is an African native fruit, of which both chemical composition and antioxidant activity against physiologically relevant reactive oxygen species (ROS) and reactive nitrogen species (RNS) were not yet investigated. It is generally accepted that the antioxidant activity of natural resources could be related with the prevention of several diseases. Baobab leaves, fruit pulp, root, stem, seeds and bark have shown medicinal properties, including diuretic, anti-inflammatory, antioxidant, hepato-protective, analgesic, anti-diarrhea, anti-dysentery, anti rheumatoid and antiviral activities.